ANALISIS SISTEM PENGENDALIAN KREDIT PADA KOPERASI REDJEKI MANDIRI JAYA RESORT SANGGAU - Kartika; Sartono; Afif, Ali; Febriati (Jurnal Akuntansi, Auditing dan Investasi, 2024)
The Redjeki Mandiri Jaya Resort Sanggau Cooperative is a cooperative engaged in the savings and loan business which functions to store funds from the public and channel them through credit. The risk of credit default always occurs in credit-providing financial institutions, so that if cooperatives are not careful in extending credit, it can cause bad credit. Adequate internal control is closely related to the credit granting system, because if internal control is not implemented adequately it will affect the credit granting system, and the risk of bad credit may occur. The author conducted this study with the aim of analyzing the credit granting system, handling bad loans, and internal control in granting credit at the Redjeki Mandiri Jaya Resort Sanggau Cooperative. This study uses qualitative research methods using data collection techniques through interviews, observation, documentation and questionnaires. Questionnaires were distributed to 8 respondents who were involved in granting credit to the Redjeki Mandiri Jaya Resort Sanggau Cooperative to find out the internal control system in the cooperative using elements according to COSO which included control environment, risk assessment, control activities, information and communication, and monitoring. The results of this study indicate that there are two factors that cause bad loans to the Redjeki Mandiri Jaya Cooperative, namely internal factors and external factors, and the impact caused by bad loans on the Redjeki Mandiri Jaya Resort Sanggau Cooperative includes reduced income, cash flow becomes stagnant, a decrease in loan balances, and a decrease in the soundness of the Cooperative. Efforts to save bad loans by the Redjeki Mandiri Jaya Resort SanggaCooperative are carried out by rescheduling, reconditioning, restructuring and liquidation